2009
DOI: 10.1177/1049731509335569
|View full text |Cite
|
Sign up to set email alerts
|

Applying Diffusion of Innovation Theory to Intervention Development

Abstract: Few social science theories have a history of conceptual and empirical study as long as does the diffusion of innovations. The robustness of this theory derives from the many disciplines and fields of study in which diffusion has been studied, from the international richness of these studies, and from the variety of new ideas, practices, programs, and technologies that have been the objects of diffusion research. Early theorizing from the beginning of the 20th century was gradually displaced by post hoc empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
327
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(363 citation statements)
references
References 57 publications
7
327
0
13
Order By: Relevance
“…It is well-known that even strong evidence in favor of a practice change does not adequately motivate adoption [13,36,52]. An assumption to the contrary is a common error that leads to ineffective dissemination [12]. This is so even in the face of elaborate, multiple, and integrated dissemination systems to publicize public health and healthcare innovations at the national level [28].…”
Section: The Role Of Vcops In Innovation Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that even strong evidence in favor of a practice change does not adequately motivate adoption [13,36,52]. An assumption to the contrary is a common error that leads to ineffective dissemination [12]. This is so even in the face of elaborate, multiple, and integrated dissemination systems to publicize public health and healthcare innovations at the national level [28].…”
Section: The Role Of Vcops In Innovation Diffusionmentioning
confidence: 99%
“…Lead users are well-known, wellconnected members of a social system who are considered especially credible by their colleagues and near-peers [21]. They are not only early adopters of innovations but more specifically informal opinion leaders whose advice is sought by others [12]. Lead users are frequently "lead rejecters" of change initiatives, too, so communicating early with them about the new resource, its purpose and function, and sharing prototype versions for their input is important for in turn being able to convince them to be featured personalities on the registry as users and contributors to the system.…”
Section: Principles For Founding An Implementation Registrymentioning
confidence: 99%
“…There are a number of reasons why this knowledge-action gap exists [16]. For example, Dearing [17] identified a number of common mistakes made when disseminating research findings and strategies shown to be effective in research settings into practice, such as assuming that evidence matters in the decision making of potential adopters, substituting researchers' perceptions for those of potential adopters, and failing to distinguish between the different roles needed for successful dissemination. Therefore, in order for crucial research and evaluation findings to reach the broadest audience possible and be effectively and widely adopted, it is important to understand how to make these findings relevant and effectively disseminate, implement, and bring them to scale in a wide variety of contexts and settings.…”
Section: Knowledge-action Gapmentioning
confidence: 99%
“…The knowledge-action gap is one of the most challenging barriers for public health practice [17], including suicide prevention. The TLC initiative, Life is Sacred Native Youth Suicide Prevention Program, and the Maine Youth Suicide Prevention Program used an adapted four-step actionable knowledge framework, informed by the best available evidence on knowledge translation, and created three very different actionable knowledge products to make their evaluation findings accessible, useful, and relevant for application in the field.…”
Section: Original Researchmentioning
confidence: 99%
“…The literature presents a set of studies identifying theories 35,58,66,67,68,69 for the prediction and explanation of mechanisms of change associated with healthcare quality improvement interventions at the macro political, organizational and social context and individual behavior levels (Table 1).…”
Section: Theoretical Basis For the Design Implementation And Evaluamentioning
confidence: 99%